Mortality and survival benefits in people living with human immunodeficiency virus initiated newly with Antiretroviral therapy irrespective of CD4 count - N., Diwakar T.; C., Raghavendra B.; N., Keerthi Kumar (International Journal of Advances in Medicine, 2020)
Background: HIV is a global pandemic with estimated 37.9 million people living with HIV(PLHIV) worldwide in which 23.3 million (62%) PLHIV take antiretroviral therapy (ART). In 2018 UNAIDS estimated 7,70,000 people died from AIDS related illness globally. India has around 21,40,000 PLHIV and 69,110 AIDS-related deaths in 2017 according to NACO report. This study aims to know the mortality and survival benefits in PLHIV newly initiated on ART as per test and treat policy. Methods: A prospective observational cohort study was conducted from June 2017 to June 2018, involving 100 ART-naïve PLHIV attending this ART Centre at Hospitals attached to BMCRI, Bangalore, India. Survival analysis was done by Kaplan Meier estimates. Spectrum of opportunistic infections and their role in cause of mortality was studied. Results: The overall survival rate was 92% at 6 months and 91% at one year after ART initiation. The mortality rate at the end of one year was 9%, out of which Pulmonary Tuberculosis is the most common cause of mortality. There was a significant increase in the CD4 count during follow up, the mean increase in the CD4 T-cell count at the end of 6 months and 12 months was 157 cells and 286 cells per cubic millimeter respectively above the baseline value. Conclusions: In this study early initiation of ART is found to be beneficial in clinical and immunological recovery with increase in CD4 counts and reduction in opportunistic infections in PLHIV. Pulmonary Tuberculosis remains the grave risk factor for mortality among PLHIV/AIDS patients on ART.